2000
DOI: 10.1074/jbc.275.7.5228
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor Rapidly Increases Activity and Cell Surface Expression of the EAAC1 Subtype of Glutamate Transporter through Activation of Phosphatidylinositol 3-Kinase

Abstract: Na؉ -dependent glutamate transporters are the primary mechanism for removal of excitatory amino acids (EAAs) from the extracellular space of the central nervous system and influence both physiologic and pathologic effects of these compounds. Recent evidence suggests that the activity and cell surface expression of a neuronal subtype of glutamate transporter, EAAC1, are rapidly increased by direct activation of protein kinase C and are decreased by wortmannin, an inhibitor of phosphatidylinositol 3-kinase (PI3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
81
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 93 publications
9
81
1
Order By: Relevance
“…These results do not exclude EAAT2 involvement in physiological platelet uptake, since it could be a platelet transporter with a slower kinetic rate and it could begin to work at higher glutamate concentrations, when EAAT1 and EAAT3 could be endangered. The EAAT2 subcellular distribution (70% in cytoplasmic fraction) could also justify its minor involvement in physiological glutamate uptake of platelet; EAAT2 could be available in platelet membranes after translocation induced by particular stimuli, as described for EAAT3 in CNS-derived cell lines [48]. It must be also underlined that GFD-8 cell line did not express any EAAT2 immunoreactivity, but clearly showed EAAT2 mRNA.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…These results do not exclude EAAT2 involvement in physiological platelet uptake, since it could be a platelet transporter with a slower kinetic rate and it could begin to work at higher glutamate concentrations, when EAAT1 and EAAT3 could be endangered. The EAAT2 subcellular distribution (70% in cytoplasmic fraction) could also justify its minor involvement in physiological glutamate uptake of platelet; EAAT2 could be available in platelet membranes after translocation induced by particular stimuli, as described for EAAT3 in CNS-derived cell lines [48]. It must be also underlined that GFD-8 cell line did not express any EAAT2 immunoreactivity, but clearly showed EAAT2 mRNA.…”
Section: Discussionmentioning
confidence: 80%
“…As recent studies have also shown that glutamate transporter expression and activity may be regulated by different endogenous or exogenous factors [6,8,10,13,15,27,31,35,44,48,53], we are now studying the possible role of physiological stimuli, such as PKC activation, or oxidative stress on glutamate transporter activation/inactivation or translocation in platelets. The final goal of these studies is the possibility of using platelets as peripheral model to investigate the role of glutamate, its transporters and its effect pathway in neurodegenerative disorders, with the clear advantage of being easy to obtain, suitable for pharmacological and clinical studies and, compared to human brain tissue studies, of being independent from postmortem or end-stage changes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that multiple agents, such as volatile anesthetics, cause acute changes of EAAT activity (9,10). In EAAT3, this acute change of activity is mediated by the redistribution of EAAT3 from intracellular compartments to the plasma membrane, the functional site of EAAT3 (9).…”
mentioning
confidence: 99%
“…Twenty-four hours after transfection, cell surface proteins were labeled with biotin and isolated (16). Cells were washed twice with cold rinsing solution (phosphate-buffered saline with Ca/Mg (1 mM MgCl 2 and 0.1 mM CaCl 2 , pH 7.35)) (27) and incubated in rinsing solution containing 1 mg/ml EZ-Link Sulfo-NHS-Biotin (Pierce) for 30 min at 4°C. Cells were washed twice with quenching solution (rinsing solution with 100 mM glycine added), incubated in quenching solution for 20 min, and solubilized at 4°C in radioimmune precipitation buffer ((150 mM NaCl, 1 mM EDTA, and 100 mM Tris-HCl, pH 7.4), 1% (v/v) Triton X-100, 1% (w/v) deoxycholate, and 0.1% (w/v) SDS containing protease inhibitors (1 g/ml leupeptin, 250 M phenylmethylsulfonyl fluoride, 1 g/ml aprotinin, 1 mg/ml trypsin inhibitor, and 1 mM iodoacetamide).…”
mentioning
confidence: 99%